Induced breeding of Clarias batrachus using “gonopro-fh” in a mini portable hatchery and study on embryonic developmental stages - Sangma, Chikambe N; Vyas, Vipin; Siddiqui, Shadab (AG Volumes, 2025)
In this study the breeding of Clarias batrachus was carried out from July to September 2023 at Barkatullah University, Bhopal, using Gonopro-FH in a portable mini hatchery setup. Mature brooders (male: 409–545 g, female: 550–605 g) were injected intramuscularly at a 1:1 sex ratio, with carefully measured hormone doses. Fertilized eggs exhibited clear morphological features, and embryonic development was monitored from cleavage to hatching. Key developmental milestones such as the morula, blastula, gastrula, somite formation, heartbeat, and eventual hatching at 22 hours post-fertilization (25.1°C) were recorded in detail. Larval behavior, pigmentation, and organ development were also observed in post-hatching. This study concludes that hormone-induced breeding using Gonopro-FH significantly enhances spawning efficiency, fertilization rate, and seed quality. These findings support the use of synthetic hormones in this fish to achieve predictable breeding cycles, improved seed production, and sustainable aquaculture practices.